Food Taboos and Cultural Beliefs among Pregnant Mothers in Rural Sindh - Sharma, Madhu Bala; Khooharo, Yasmeen Nawaz; Mehmood, Misbah Mehmood; Asif, Bushra (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To identify food beliefs, dietary practices and their determinants among pregnant women of rural Sindh. Methodology: This cross-sectional study involved 180 pregnant women attending antenatal clinic of Muhammad Medical and Dental College. Participants were selected randomly.Inclusion criteria were pregnant women with any gestational age. Exclusion criteria were those pregnant women with any obstetrical emergency attending O.P.D. Information was collected on preformed questionnaire by interviewing pregnant women from July 2020 to December 2020. Information about their sociodemo-graphic features, food beliefs and taboos and their knowledge about dietary intake in pregnancy was recorded. Data was analysed using SPSS version 22. Descriptive analysis was performed. Chi-square test is used to assess the association. P value of <0.005 was considered to be significant. Results: In a total of 180 women selected for the study, 98% women believed that women should take good diet and increase calorie intake during pregnancy, but majority (90%) of participants had some kind of food taboos and beliefs during pregnancy. Most protein rich food avoided were classified as ‘hot foods’ considered to cause abortion and preterm birth. Orange, bananas were considered as ‘cold foods’ and lead to sore throat and cough. Dry fruits were avoided because of belief that these will increase birth weight of foetus. Conclusion: Majority of the pregnant mothers were observed to follow one or more food taboos irrespective of parity, gestational age, monthly income, occupation and educational status with significant association. Key words: Food taboos, Cultural, Beliefs, Pregnant, Mothers, Rural Sindh